A split strategy to prevent cytomegalovirus after kidney transplantation using prophylaxis in serological high‐risk patients and a pre‐emptive strategy in intermediate‐risk patients: Combining the best of two options?. Issue 2 (22nd October 2020) - Hellemans, Rachel; Wijtvliet, Veerle; Bergs, Kristof; Philipse, Ester; Vleut, Rowena; Massart, Annick; Couttenye, Marie‐Madeleine; Matheeussen, Veerle; Abramowicz, Daniel
Abstract: Background: Cytomegalovirus (CMV) remains an important challenge after kidney transplantation. Current Transplantation Society International Consensus Guidelines recommend antiviral prophylaxis or pre‐emptive therapy for high‐risk CMV‐seronegative recipients with a CMV‐seropositive donor (D+/R−) and moderate‐risk CMV‐seropositive recipients (R+). However, a split strategy according to CMV serostatus is not specifically mentioned. Methods: We evaluated a split strategy to prevent CMV infection after kidney transplantation in which D+/R− patients received valganciclovir (VGC) prophylaxis for 200 days, and R + patients were treated pre‐emptively according to CMV DNAemia. Patients were followed until 1‐year post‐transplant. Results: Between April 2014 and March 2018, 40 D+/R− and 92 R + patients underwent kidney transplantation. Forty‐six percent received antithymocyte globulin (ATG) induction, and 98% was treated with calcineurin inhibitors, mycophenolic acid (MPA), and steroids. No D+/R− patient developed CMV disease during prophylaxis (median 200 days), but 15% developed post‐prophylaxis or late‐onset disease. Fifty‐three percent developed neutropenia during prophylaxis, including 16/40 (40%) grade 3 or 4 neutropenia requiring reduction/discontinuation of MPA (30%) and/or VGC (35%), and an occasional need for granulocyte colony‐stimulating factor (5%). In the R + group, 40% received antiviral therapy for a median duration of 21 days; 5% developed early‐onset CMV disease. Only 5% developed neutropenia. D+/R + status (hazard ratio (HR) 2.09, P =  .004) and ATG use (HR 2.81, P  < .0001) were risk factors for CMV reactivation. Conclusions: Prophylaxis leads to acceptable CMV control in high‐risk patients but comes with a high risk of neutropenia. Pre‐emptive therapy is effective and limits drug exposure in those at lower risk of CMV.